Revalorización De Bienes En La Gobernación De La Provincia De Los Ríos - García Sánchez, Stalin Santiago (2019)
Over the years in the public sector, the revaluation has become something not necessary, which is why most public entities have not been executing this action. This case study is part of the research sub-line: Financial Management and Social Commitment, which allows me to manage, provide a real revaluation to the assets owned by the Government of the Province of Los Ríos, the tools that demonstrate the sufficiency of goods, the activities that are carried out and the social responsibility that this entails; since the government apart from being an institution is one where the requirements of citizens of any kind are accepted and for the resolution of them, all the goods must be available in optimal conditions. A revaluation is produced when the values ​​of the assets increase in the market. In this case, when an asset is acquired it comes with its stipulated value, but as the years recur, the value of said asset must be updated.